Enhancing motivation through music videos with lyrics, downloaded from You Tube for the reading comprehension process of eighth graders at Estados Unidos de América, Junior High School - Miranda Cáceres, Kathia Marisol (UDELAS, 2013)
The development of this research is focused on diagnosis of causes and effects of the development of classroom motivation in learning english in Junior High School students, whose main contribution is to stimulate interest in teaching a second language through music video as a technique for the reading comprehension process in an enjoyable and funny environment, thus, to avoid monotonous classes and lack of interest by the students.